Information policy as a resource for state management - O. A. Sudorgin; V. G. Ivanov; V. F. Nitsevich; O. A. Nesterchuk (Управление)
This article examines the multifaceted nature of information policy and the key role played by various social institutions in its formation and implementation. It also explores the participation of political parties, movements and associations of citizens as key actors responsible for the formation and implementation of information policy. In addition, the authors analyze the significant influence of political parties on state power in matters of information policy, citing examples from such modern countries as Russia and the United States. The enduring importance of political parties as vital social institutions is recognized, their role in the information space and their impact on society when coming to power are discussed. The mechanisms of relations between the institutions of state power and the mass media are studied, and their characteristics are given, taking into account the interests of both sides in the field of modern communications. The main directions of using public relations for political reasons by governing bodies are highlighted, taking into account the increased expectations of social responsibility, activity and consciousness on the part of other participants in the political process and civil society. The effective management of the process of institutionalization of information policy is considered.